Online cooperative learning: exploring perspectives of pre-service teachers after the pandemic - Nisha Chakyarkandiyil; G. S. Prakasha (International Journal of Evaluation and Research in Education (IJERE), 2024)
Mainly, research has explored pre-service teachers’ perspectives toward cooperative learning within face-to-face teaching. However, in a postpandemic scenario, previous research has yet to effectively explore preservice teachers’ (PSTs) perspectives toward online cooperative learning (OCL) in teacher education programs. So, recognizing the gap in the literature, this paper aims to explore the perspectives of PSTs towards OCL. The researchers employed a qualitative research design for the present study. The researchers conducted semi-structured interviews with 10 PSTs who underwent OCL during the pandemic. These PSTs may possess digital proficiency, virtual collaboration abilities, flexibility in evolving educational environments, and an enhanced understanding of online cooperative learning methodologies within modern education. Researchers employed a thematic analysis to analyze the qualitative data obtained. The various themes that emerged from the study are perceived benefits of OCL, challenges to OCL, technological proficiency, learning strategies and support, and building a supportive online learning community. Future researchers may contribute to advancing effective online learning practices by gaining a deeper understanding of pre-service teachers’ perspectives towards OCL through research on a larger scale, including various teacher education programs in various countries.